Five Novel Mutations Located in Exons III and IX of the Protein C Gene in Patients Presenting With Defective Protein C Anticoagulant Activity - Gandrille, Sophie; Alhenc-Gelas, Martine; Gaussem, Pascale; Aillaud, Marie-Françoise; Dupuy, Evelyne; Juhan-Vague, Irène; Aiach, Martine (Blood, 1993)
We describe five families presenting with type II hereditary protein C deficiency characterized by normal antigen and amidolytic activity levels but low anticoagulant activity. All the exons and intron/exon junctions of the protein C gene were studied using a strategy combining amplification by the polymerase chain reaction (PCR). denaturing gradient gel electrophoresis of the amplified fragments, and direct sequencing of fragments displaying altered melting behavior. We detected five novel mutations. Three were located in the C-terminal part of the propeptide encoded by exon III: Arginine (Arg)-5 to tryptophan (Trp), Arg-1 to histidine (His), and Arg-1 to cysteine (Cys) mutations. The two others, located in exon IX, affected Arg 229 and serine (Ser) 252, which were respectively replaced by glutamine (Gin) and asparagine (Asn). DNA studies of the other exons from affected individuals showed no other abnormalities. These novel mutations provide further insight into the importance of the affected amino acids located close to the active site, near Asp 257, one of the three amino acids of the catalytic triad. The low anticoagulant activity of the abnormal protein C indicated that Arg 229 and Ser 252 play a key role during the interaction between protein C and its cofactor protein S, phospholipids, or factors Va and Villa. The Arg-1 to Cys mutation led to the dimerization of protein C with another plasmatic component, as evidenced by the presence in the plasma of a high molecular weight form of protein C that disappeared after reduction. No molecular mass abnormalities were observed in heavy and light chains of all other protein C mutants. In the five families explored, 9 (64%) of the 14 subjects bearing the mutations reported thrombotic events. This suggests that the protein C amino acids affected by the mutations are very important for the in vivo expression of the antithrombotic properties of protein C.